2013
DOI: 10.1080/19393210.2013.845249
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and micronutrient elements in organic, brown and polished rice in Brazil

Abstract: Concentration levels of As, Cd, Hg, Pb, Tl, Sn, Sb Co, Cu, Mn, Se, Zn, Cr, Ni and Mo in different types of rice cultivated in irrigated fields in Brazil were evaluated. Arsenic, Cd, Pb, Zn, Mn and Cu were found in higher concentrations in brown rice samples, suggesting the prevalence of these elements in the bran. Meanwhile, lower concentrations of Pb, Mo, Cr, Se and Co were found in parboiled rice. Organic rice did not differ of cultivated conventionally rice. Thallium, Hg and Sb were not detected in any rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The detected mean level of lead in rice samples was 23.5% of the upper limit of 0.2 µg/g permitted in food. The mean detected lead levels in this study were higher than the levels found in Chinese rice (0.028 ± 5.6 µg/g; Fu et al, 2012) but similar to the detected level in Brazilian rice with a mean level of 0.057 µg/g (Poletti et al, 2014). The observed high levels of toxic elements (As, Pb, Cd) in this study could be due to heavy soil pollution arising from indiscriminate waste disposal system, vehicular pollution and contamination with petroleum products (Huang et al, 2006).…”
Section: Levels and Dietary Intakes Of Toxic Elements In Rice Samplesmentioning
confidence: 40%
“…The detected mean level of lead in rice samples was 23.5% of the upper limit of 0.2 µg/g permitted in food. The mean detected lead levels in this study were higher than the levels found in Chinese rice (0.028 ± 5.6 µg/g; Fu et al, 2012) but similar to the detected level in Brazilian rice with a mean level of 0.057 µg/g (Poletti et al, 2014). The observed high levels of toxic elements (As, Pb, Cd) in this study could be due to heavy soil pollution arising from indiscriminate waste disposal system, vehicular pollution and contamination with petroleum products (Huang et al, 2006).…”
Section: Levels and Dietary Intakes Of Toxic Elements In Rice Samplesmentioning
confidence: 40%
“…Market based surveys comparing conventional and organic grown brown rice have found higher total As and iAs in organic rice as compared to conventional rice ( Menon et al, 2020 ; Rahman et al, 2014 ; Segura et al, 2016 ). However, others have reported no difference ( Poletti et al, 2014 ). The multiple factors that impact As transformation and availability in the soil, differences in soil properties, cultural management practices, and choice of variety may explain these variable reports.…”
Section: Resultsmentioning
confidence: 99%
“…incorporation of straw or animal manure) ( Hossain et al, 2021 ; Ma et al, 2014 ; Norton et al, 2013 ). Market survey results of As in rice are not consistent ( Poletti et al, 2014 ) and may reflect the diverse spectrum of organic production methods, environments, and post-harvest processing treatments. Additionally, post-harvest processing, including fermentation is a potential technique in reducing heavy metal exposure in food ( Massoud et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A great amount of arsenic is removed during the rice polishing [ 21 , 50 52 ]. Besides, variation in the arsenic concentration may occur due to different cultivars, geography, environment, water quality, and growth conditions [ 21 , 24 , 25 , 29 , 30 , 37 , 51 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%